O czym informują przedsiębiorstwa w swoich raportach społecznych? - Brzozowski, Tomasz (What Do Companies Inform in Their Social Reports of?, 2009)
Social reporting is one of key elements of Corporate Social Responsibility. Still increasing involvement in social activity among Polish companies permits to study practices of reporting. There are two issues which seem especially interesting: first, a range of information disclosed in social reports, and second, a number and kind of used social performance indicators. The results of social reports analysis indicate that reports are strongly diversified in this respect. The author of the article calls for the use of reporting standardization.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 116-125